1257. A phase II Prospective Randomized Study to Assess Ceftolozane-Tazobactam in the Management of Febrile Neutropenia in Patients with Hematological Malignancies. (31st December 2020) - Chaftari, Anne-Marie; Hachem, Ray Y; Malek, Alexandre; Mulonovich, Victor; Szvalb, Ariel D; Jiang, Ying; Ali, Shahnoor; Deeba, Rita; Chaftari, Patrick; Raad, Issam I; Raad, Issam I
Abstract: Background: Despite the implementation of successful antibiotic stewardship programs, antibiotic resistance continue to emerge particularly against gram-negative bacteria. With the increase use of antibiotics in high risk patients with hematological malignancies, the empiric therapy with standard antibiotic could be inappropriate. New antibiotics may be useful to cover potential resistant pathogens. We evaluated the role of a new cephalosporin /β-lactamase inhibitor ceftolozane-tazobactam (C/T) in comparison to standard of care (SOC) antibiotics in the empiric treatment of febrile neutropenic cancer patients with hematological malignancies. Methods: We conducted a prospective randomized open label comparative study to evaluate the safety and efficacy of C/T vs SOC antibiotics consisting of cefepime, piperacillin-tazobactam or meropenem when used in combination with gram positive antibacterial agents. Between May 2018 and March 2020, we enrolled 88 febrile neutropenic patients with hematological malignancies who presented to our emergency center. Patients received at least 72 hours of intravenous study drugs and were followed through end of IV therapy and for up to 42 days. Results: A total of 88 patients were analyzed of whom 42 received C/T and 46 SOC antimicrobial agents. The rate of documented bloodstream infections was similar in both groups (CE-TZ 21% vs SOC 26%, p=0.61). Favorable clinical response at end of IV therapy was significantly better in the C/T arm compared to SOC therapy (88% vs 72%, p=0.039), at test of cure (21 days), and last follow-up (42 days). In patients with documented infections, the rate of microbiological eradication was similar in both groups. Drug-related adverse events that led to drug discontinuation was similar in both groups (7%). Similarly overall mortality was similar in both groups. Conclusion: The empiric use of C/T to cover gram negative organisms in high risk febrile neutropenic patients with hematological malignancies is safe and associated with better clinical outcome than SOC antimicrobial agents. The emergence of resistant pathogens should be further evaluated. Disclosures: Issam I. Raad, MD, Citius (Other Financial or Material Support, Ownership interest)Cook Medical (Grant/Research Support)Inventive Protocol (Other Financial or Material Support, Ownership interest)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Ownership interest)